2007
DOI: 10.1007/s00395-007-0673-0
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-alpha antagonism protects from myocardial inflammation and fibrosis in experimental diabetic cardiomyopathy

Abstract: To investigate the effect of anti-cytokine-based therapy in the course of diabetic cardiomyopathy, we performed a study using an anti-TNF-alpha monoclonal antibody treatment (mab) in Sprague male Dawley (SD) rats with streptozotocin-induced diabetic cardiomyopathy. Five days after streptozotocin injection, rats were treated with the anti-TNF-alpha mAb C432A for 6 weeks.At the end of the study, left ventricular (LV) function was determined by a pressure-catheter. Intercellular adhesion molecule (ICAM)-1, vascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
121
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(135 citation statements)
references
References 43 publications
11
121
0
3
Order By: Relevance
“…Consistent with our findings in these mice, nontransgenic models of lipid overload using long-term high-fat diet or streptozotocin treatment have also demonstrated increased numbers of macrophages within the hearts of insulin resistant and/or diabetic mice (13,30). However, assessing the influence of cardiac macrophages on LV function using cell depletion strategies with these models is confounded by the concomitant role of macrophages in promoting the primary dysregulation of systemic metabolism, which is further modified by macrophage depletion (16,21).…”
Section: Discussionsupporting
confidence: 77%
“…Consistent with our findings in these mice, nontransgenic models of lipid overload using long-term high-fat diet or streptozotocin treatment have also demonstrated increased numbers of macrophages within the hearts of insulin resistant and/or diabetic mice (13,30). However, assessing the influence of cardiac macrophages on LV function using cell depletion strategies with these models is confounded by the concomitant role of macrophages in promoting the primary dysregulation of systemic metabolism, which is further modified by macrophage depletion (16,21).…”
Section: Discussionsupporting
confidence: 77%
“…5A) supported the conclusion that JNK mediated HGinduced caspase-3 activation and intrinsic apoptotic pathways. TNF-a, which is increased by HG induction, also induces cardiac apoptosis through its type 1 receptor complex II, a classic death receptor (18). The binding between TNF-a and TNF-a type 1 receptor complex II results in the activation of the JNK-dependent caspase cascade and then commits cells to apoptosis (40).…”
Section: Discussionmentioning
confidence: 99%
“…Two groups have shown that TNF provokes cardiomyocyte apoptosis and cardiac remodeling through the activation of multiple cell-death pathways under diabetic conditions and in the pressure overload state, respectively (16,17). Intervention against TNF-a using a specific antagonist was reported to protect against cardiac inflammation, apoptosis, and fibrosis in experimental diabetic cardiomyopathy (18). This suggests that inhibition of inflammatory cytokines may be an effective strategy for the prevention of diabetes-induced pathogenic changes in the heart.…”
mentioning
confidence: 99%
“…Additionally, we have documented that increased plasma N-terminal brain natriuretic peptide levels in patients with chronic rheumatic valve disease is a potential marker of disease severity and correlates with symptoms (Davutoglu et al 2005b). However, it is well documented that cytokines like TNF-alpha increase intramyocardial inflammation and cardiac fibrosis and thus may lead to cardiomyopathy (Westermann et al 2007). Furthermore, attenuation of development of experimental cardiomyopathy by the antagonism of such cytokines has been documented (Suzuki et al 2007).…”
mentioning
confidence: 99%